Adaptación y análisis factorial exploratorio del cuestionario errores/problemas en el uso del condón masculino (cues) - Hernández Torres, José Luis; Benavides Torres, Raquel Alicia; Quiroz Guerra, Alma Rosa; Martínez Cervantes, Roxana; Cárdenas Cortés, Adriana Mayela; Rodríguez Vázquez, Nancy (Universidad Autónoma de Nuevo León, 2020)
In México, the Human Immunodeficiency Virus (HIV) is contracted mainly in youth since it presents a rate of 3.3 cases per 100.000 young people between 15 and 29 years of age, in this sense the development of new prevention technologies such as HIV vaccines and microbicides continue to advance, but condoms continue to be the main means of prevention, currently there are few instruments that help measure errors and problems in the use of the male condom. The objective of the present study was to determine the factorial structure of the adaptation of the questionnaire errors/problems in the use of the male condom (CUES) in 143 young users of a non-governmental organization dedicated to the diagnosis and prevention of HIV in the city of Monterrey Nuevo León, México, for which a calculation of Bartlett and Kaiser-Meier Olkin (KMO) sphericity coefficients was conducted, using a Varimax rotation calculation between items, in addition to determining internal consistency using Cronbach's alpha. The results indicated that the condom use error/problem questionnaire (CUES) reported a Barlett sphericity statistic with X2 = 965.8 df = 120 p < 0.001 that suggests a high linear correlation between the items analyzed and an adequacy test of KMO of 0.83 referring to a high correlation and sample adequacy. Cronbach's alphas reported greater adjustment between factors than in their global score. It is suggested to continue analyzing the CUES towards a confirmatory analysis to determine the adjustment in order to confirm the number of factors to achieve an acceptable validity in the Mexican population.